Core temperature responses of male football players during matches in the heat - Associations with physiological and running demands - Schwarz, E.; Oliveira, C. B.; Duarte Muñoz, M.; Alanis, A.; Alanis, M.; Lara, A.; Freeze, A.; Costa, J. A.; Eckerle, L.; Meyer, T.; Duffield, R. (Journal of Science and Medicine in Sport, 2025)
Objectives This study describes core temperature (Tcore) responses during football matches in warm to hot conditions. It aims to identify which physiological, running, and perceptual factors are associated with reaching high Tcore values while controlling for environmental conditions and cooling. Design Forty highly trained male youth football players participated in at least two out of four matches held at temperatures between 26 and 42°C. In three matches, heat mitigation strategies (passive rest and 17°C drinks, or cold towels and 5°C drinks) were applied pre-match, at half-time, and in additional breaks per half. Methods Match running, heart rates, hydration markers, and perceptual responses were measured and checked for associations with peak Tcore values via linear mixed models accounting for environmental conditions and heat mitigation strategies. Results Peak Tcore was 39.2±0.5°C (range: 37.9-40.1°C). Higher total distance (ß=0.39 [0.13, 0.64], p=0.004) and distance at low-to-moderate speeds (ß=0.44 [0.18, 0.69], p=0.001) were associated with higher peak Tcore, while walking distance was inversely associated (ß=-0.42 [-0.69, -0.15], p=0.003). High-speed and sprinting distances were not associated with peak Tcore. Higher heart rate (ß=0.37 [0.10, 0.64], p=0.008), sweat loss (ß=0.38 [0.14, 0.62], p=0.002) and body mass loss (ß=0.20 [0.00, 0.40], p=0.047) were also associated with higher peak Tcore. Rating-of-fatigue (p=0.74), perceived exertion (p=0.78), and thermal sensation (p=0.98) were not associated with peak Tcore. Conclusions High Tcore peaks were observed in all conditions and were associated with higher heart rate, sweat loss, and match running. Covering more distance at low-to-moderate speed was associated with a higher heat strain, whereas walking more (instead of running) was associated with lower Tcore peaks.